SUCCESS FACTORS OF ACCOUNTING INFORMATION SYSTEM IN PT. KUNCIMAS NIAGATAMA BANYUWANGI - Nofita Ambarwati; Muhammad Firdaus; Nanda Widaninggar (MBA - Journal of Management and Business Aplication, 2020)
This study aims to analyze the factors that influence the success of the accountinginformation system at PT. Kuncimas Niagatama Banyuwangi. The success of accountinginformation systems is influenced by Human Behavior in Organizations, ManagementSupport, Motivation and Training, Data Processing in the System, and Management andImplementation Process. This study used the primary data by total sample of thirty-fiveemployees and used the purposive sampling technique. The quality of the questionnaire wastested using the validity test and reliability test. Data analysis used multiple regressionanalysis, which includes the classic assumption test, t test and the coefficient of determinationThe results showed that Human Behavior in Organizations, Motivation and Training,Management and Implementation Process significantly influence the Success of AISImplementation. Only Management Support variable and Data Processing in the System haveno significant effect on the Success of AIS Implementation.